AGE DIFFERENCE IN RESOURCE ALLOCATION PREFERENCE: THE ROLE OF MORTALITY SALIENCE AND FUTURE TIME PERSPECTIVE. (16th November 2018) - Chen, A; Fung, H; Chu, S
Abstract: This study aims at contrasting the effects of limited future time perspective and mortality salience on goal prioritization across adulthood. Socioemotional selectivity theory (SST) argues that people increasingly prioritize emotionally meaningful goals when they perceive future time as more limited. Meanwhile terror management theory (TMT) suggests that mortality salience (i.e. the awareness of one's mortality) drives people to prioritize the goal of perpetuating own existence through affirming cultural worldview. We recruited 432 participants and randomly assigned 6 experimental conditions: Limited Time condition, Mortality Salience condition, Death Reflection condition, 2 combined conditions and control condition. Through Mixed Model Analysis, the result support our hypothesis that older adults would allocate more resources to targets who are more emotionally close and more worldview affirming. Furthermore, Limited Time condition and Mortality Salience condition made older adults but not younger adults more likely to select the emotionally close and world-view confirming social partners. Death Reflection condition had to be combined with LT to show similar effects. In contrast with our prediction, targets who were just emotionally close or just world-view confirming were not favored in resource allocation.Together, these results show that compared with younger adults, older adults tend to prioritize emotionally meaningful goals as well as worldview supporting goals. This process could be intensified by limited time perspective and mortality salience but not solely concrete death-related thoughts in older group.